Negativity in Play - How Negative Emotions create Meaningful Games - Umbelino, Mateus A. M.; Mota, Rosilane Ribeiro da (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais Estendidos do XX Simpósio Brasileiro de Jogos e Entretenimento Digital, 2021)
Emotions are considered a core component of any media experience, including video games. However, most research regarding video game experiences regularly focus on the positive emotions elicited during play. As research on negatively valenced emotions is still ongoing, recent studies show they can provide more meaningful experiences for players. Therefore, this paper seeks to build upon previous research to emphasize how negatively valenced emotions can benefit the player experience (PX). Accordingly, studies regarding psychological research, essays, and presentations focused on game design are analyzed and discussed. A closing section of this paper serves as an examination of the game Getting Over It With Bennet Foddy, whose thematic and design philosophy complement those explored by this paper.